Building an Occupational Safety Behavior in an Organization - Vebi Dewi Supartini; Anggraini Sukmawati (Binus Business Review, 2019)
This research discussed human resources development with occupational safety behavior. The role of each category was in accordance with occupational safety behavior and employee job satisfaction. The researchers used a systematic search methodology by identifying articles related to employee occupational safety behavior and the factors that could influence it. Factors that influenced occupational safety behavior included motivation, occupational safety behavior, leadership, and job satisfaction. This research contributes to the development of human resources in the workplace in the form of employees’ safety interests. The results show the importance of implementing occupational safety behavior in an organization. It can be an implementation of human resource development. Factors that can be considered in occupational safety behavior are motivation, leadership, and job satisfaction. Therefore, it is necessary to determine the workplace of employees in an organization. It is to ensure the safety of employees by taking organizational safety procedures for employee satisfaction.